Integrating Qualitative and Social Science Factors in Archaeological Modelling - Saqalli, Mehdi; Vander Linden, Marc.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book covers the methodological, epistemological and practical issues of integrating qualitative and socio-anthropological factors into archaeological modeling. This text fills the gap between conceptual modeling (which usually relies on narratives describing the life of a past community) and formalized/computer-based modeling which are usually environmentally-determined. Methods combining both environmental and social issues through niche and agent-based modeling are presented. These methods help to translate data from paleo-environmental and archaeological society life cycles (such as climate and landscape changes) into the local spatial scale. The epistemological discussions will appeal to readers as well as the resilience socio-anthropological factors provide facing climatic fluctuations. Integrating Qualitative and Social Science Factors in Archaeological Modelling will appeal to students and researchers in the field. Features the integration of socio-anthropological factors (such as inheritance or locality) into conceptual modeling; Contains several examples of formalization case studies; each one describing a method dealing with socio-anthropological factors; Includes an epistemological analysis of the way factors are integrated and/or formalized for reducing the gap between environmentally-deterministic and socio-anthropological-formalized modelling.
Introduction -- O tempora O mores : Building an epistemological procedure for modeling socio-anthropological factors: stakes, choices, hypotheses and constraints -- From culture difference to a measure of ethnogenesis -- Modeling niche construction in Neolithic Europe -- A new reading of the French Bronze Age using data from development-led archaeology: Bronze Age survey database (DatABronze) -- What can a MAS tell us about the Bantu migrations 3000 years ago? -- The evolutionary transition from biologically to culturally based social systems: Qualitative modeling issues -- Data models, connectivity between sites and the chaîne opératoire approach: the chalcolithic southern levant as a case study -- Conclusion. .
Keywords: Sociology -- Methodology; Computer simulation; Archaeology; System theory; Ethnology; Sociological Methods; Computer Modelling; Archaeology; Complex Systems; Sociocultural Anthropology